Effects of different metaphor usage on hypertext learning - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2011)
There are many studies that offer different opinions on the effects of hypertext usage as an educational tool. Given the differences of opinion, it is useful to research the effects of metaphor usage in hypertext education and the use of hypertext as an educational tool. In this study, the effects of metaphors' uses in constructing the characteristics of the hypertext teaching have been approved. A between-group design experiment was conducted to study the effects of four metaphors on four different groups. Survey results emphasise the importance of metaphor usage and the manner in which metaphor is used. It was also discovered that metaphor usage in the hypertext teaching affects the construction duration of the hypertext but does not have any effects on the acquisition of knowledge.
Keywords: metaphor; hypertext; teaching/learning strategies; media in education; knowledge acquisition; INTERFACE METAPHORS; SPATIAL METAPHORS; KNOWLEDGE